Assessment as Instruction in Feedback on L2 Writing Tasks - Shakra, Zena Abu (European Scientific Journal, ESJ, 2023)
This paper builds on previous research which demonstrated how writing instruction in the field of SLA should revisit instructional methodology which proports to create autonomous learners highlighting how a broader conceptualization of feedback on learner production is required. The present study expands on the original research by exploring how conventional attempts at increasing learner autonomy and stimulating metacognitive activity through feedback on writing tasks are often not sufficient. It explores how feedback used to assess L2 writing takes on a more instructional quality as it is reduced in scope focusing only on selected sections of writing. The study not only describes the discourse which characterizes scaffolded attempts to foster autonomy on a writing tasks during conferences when feedback is restricted to only one specific section of the draft, but also compares it with similar scaffolded writing conferences that involve more substantial feedback on writing. Findings suggest that minimizing feedback during assessment has a more positive effect on learner discourse and learner visualization of the learning process. Paradoxically, curtailing feedback which is in fact purported to facilitate learning and task acquisition during the assessment of writing tasks, actually renders it more instructional thus resulting in more positive outcomes for both the instructor and L2 learner. The theoretical implications of this are then discussed.